1988
DOI: 10.1093/cvr/22.10.679
|View full text |Cite
|
Sign up to set email alerts
|

Depressed baroreflex control of renal nerve activity in conscious WHHL rabbits

Abstract: The baroreflex control of heart rate and renal nerve activity were examined in conscious Watanabe heritable hyperlipidaemic (WHHL) rabbits. Normal Japanese white rabbits were used as controls. The concentrations of serum cholesterol and triglyceride in WHHL rabbits were ten times higher than those in normal rabbits. The basal values of mean arterial pressure, pulse pressure and heart rate in WHHL rabbits were significantly higher than those in normal rabbits. Baroreceptors were stimulated or unloaded by raisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indeed, it has been demonstrated that baroreflex control of sympathetic renal nerve activity is depressed in conscious WHHL rabbits. 18 Thus, the Ang II-induced increase in arterial blood pressure may elicit a smaller reduction in sympathetic nerve activity directed to the resistance vessels and, hence, may add to the enhanced vascular responsiveness to Ang II in vivo. There are several levels at which atherosclerosis can blunt the baroreflex.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that baroreflex control of sympathetic renal nerve activity is depressed in conscious WHHL rabbits. 18 Thus, the Ang II-induced increase in arterial blood pressure may elicit a smaller reduction in sympathetic nerve activity directed to the resistance vessels and, hence, may add to the enhanced vascular responsiveness to Ang II in vivo. There are several levels at which atherosclerosis can blunt the baroreflex.…”
Section: Discussionmentioning
confidence: 99%
“…The control capacity of the baroreflex AP control system progressively decreased with time after massive hemorrhage and tended to recover somewhat by 110 min after hemorrhage. Therefore, the evaluation of the baroreflex AP control capacity under the hypovolemic conditions due to massive hemorrhage, including estimation of time-dependent effects of anesthetics, is not considered to show the precise control capacity of the system because massive hemorrhage must be a parametric forcing which modifies the normal characteristics of the baroreflex AP control system [6][7][8][9][16][17][18].…”
Section: Discussionmentioning
confidence: 99%